Application of a Proposed Algorithm to Cesarean Deliveries for Nonreassuring Fetal Heart Rate Tracing - Berger, Dana Senderoff; Crosland, Adam; Newman, Rachel; Bosse, Bradley; Makhoul, Joshua; Chan, Kenneth; Seet, Emily L. (American Journal of Perinatology, 2021)
Objectives The aim of the study is to evaluate how current management of Category II fetal heart rate tracings compares with that suggested by a published algorithm and whether these differences lead to disparate neonatal outcomes.Study Design This is a retrospective observational study from the resident service at an academic-community tertiary care center from 2013 to 2018. We reviewed archived fetal heart rate tracings from patients with cesarean delivery performed for nonreassuring fetal heart rate tracing and interpreted tracings against the algorithm. We assigned tracings to one of three categories: Group A—consistent; Group B—inconsistent too early (algorithm permits the patient to labor longer); Group C—inconsistent too late (algorithm suggests performing the cesarean delivery sooner). Maternal demographics, features of labor, and neonatal outcomes were compared.Results Of the 110 cases, 27 (24.5%) had a cesarean delivery performed in group A, 49 (44.5%) in group B, and 34 (30.9%) in group C. Baseline characteristics were similar. Of the 49 in group B, 46 (93.9%) violated the algorithm at the same branchpoint. In group C, cesarean deliveries would have been performed on average 244 minutes earlier had the algorithm been used. Neonatal outcomes were not significantly different among the groups, including 5-minute Apgar <7, pH <7.1, and NICU admit.Conclusion Our retrospective application of the algorithm showed that 44.5% of patients who have cesarean delivery for nonreassuring fetal heart rate tracing may be able to labor longer and that violation at a common decision point on the algorithm (moderate variability or accelerations, but a lack of recurrent decelerations) is responsible for nearly all such cesarean deliveries. More studies are needed to evaluate if cesarean delivery rates for nonreassuring fetal heart rate tracing can be reduced without impacting neonatal outcomes using the algorithm.Key Points
Keywords: nonreassuring fetal heart rate tracing; Category II fetal heart rate tracing; cesarean delivery; intrapartum fetal heart rate; acidosis; fetal distress